MOLECULAR CHARACTERIZATION AND GENETIC DIVERSITY ANALYSIS IN FOUR BRASSICA SPECIES USING MICROSATELLITE MARKERS - PRAJAPAT, PRAVIN; N. SASIDHARAN,; KUMAR, MUKESH; PRAJAPATI, VIJAY (The Bioscan, 2014)
The genus Brassica consists of a broad range of oilseed, vegetable and condiment crops with high degree of genetic diversity and is one of the most important oilseed crops in India with little information on genetic diversity. Therefore, genetic diversity analysis of 30 Brassica genotypes belonging to four cultivated species was assessed using 24 SSR markers. With a 72% polymorphism, a total of 84 alleles varied from 1 to 8 (BRMS 14) with a mean of 2.79 alleles were observed. Nine, out of 24 SSRs produced 100% polymorphism. The amplicon size ranged from 99bp (BRMS-26) to 383bp (BRMS-31). The highest allele frequency of 0.933 was for BRMS-03 and BRMS-17 whereas PIC ranged from 0.79 (BRMS-31) to 0.12 (BRMS-003). BRMS-17 gave specific bands for B. carinata. In four clusters, all 30 accessions were grouped into their respective clusters on the basis of species. Analysis revealed 2.11, 0.38, and 0.56 effective allelic numbers (Ae), the observed heterozygosity (Ho) and expected heterozygosity (He), respectively. The study emphasized that species specific primers can be employed to discriminate between the species and that SSR markers can be a useful tool in the germplasm characterization of Brassica species as well as in various breeding programs.